1999
DOI: 10.1128/aac.43.1.194
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Six New Fluoroquinolones against Brucella melitensis

Abstract: We have tested the in vitro activities of eight fluoroquinolones against 160 Brucella melitensis strains. The most active was sitafloxacin (MIC at which 90% of the isolates are inhibited [MIC90], 0.12 μg/ml). In decreasing order, the activities (MIC90s) of the rest of the tested fluoroquinolones were as follows: levofloxacin, 0.5 μg/ml; ciprofloxacin, trovafloxacin, and moxifloxacin, 1 μg/ml; and ofloxacin, grepafloxacin, and gatifloxacin, 2 μg/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 14 publications
2
19
1
2
Order By: Relevance
“…The efficacy of fluoroquinolones in the treatment of brucellosis has been shown both in vitro and in vivo [45]. Although most studies failed to prove the efficacy of quinolones as monotherapy for brucellosis [46], their inclusion in combination regimens is an accepted, though significantly more expensive, variation of the classical treatment [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of fluoroquinolones in the treatment of brucellosis has been shown both in vitro and in vivo [45]. Although most studies failed to prove the efficacy of quinolones as monotherapy for brucellosis [46], their inclusion in combination regimens is an accepted, though significantly more expensive, variation of the classical treatment [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of two recent-generation fluoroquinolones, moxifloxacin and gatifloxacin, against Brucella spp. has been determined in vitro in a number of studies that include reported MIC 90 values (minimum inhibitory concentration for 90% of the organisms) of 0.125 g/mL [2], 1 g/mL [3] or 8 g/mL [4] for moxifloxacin and 2 g/mL [3] or 4 g/mL [5] for gatifloxacin. In one study, the MIC 90 values for moxifloxacin and gatifloxacin against 160 strains of Brucella melitensis were found to be 1 g/mL and 2 g/mL, respectively [3], highlighting the efficacy of the antibiotics against a wide range of strains.…”
Section: Introductionmentioning
confidence: 99%
“…As Brucella species are intracellular pathogens, the treatment requires not only combined regimens but agents that may efficiently penetrate macrophages as well [2,3]. The type of antibiotics used for treatment of brucellosis influences the recurrence rate and it is clear that a synergistic combination with marked intracellular activity is the best therapeutic regimen in Brucellosis [4].…”
Section: Introductionmentioning
confidence: 99%